Campaign of hate [videorecording (DVD)] : Russia and gay propaganda - Lucas, Michael, 1972-; Lucas, Michael, 1972-; Gessen, Masha (QC Cinema, 2014)
As most of the world moves forward toward gay equality, Russia is seemingly heading backward. In 2013, the Russian parliament passed a ban on so-called 'gay propaganda' that effectively makes nearly any public discussion of gay equality a crime. Violent attacks against Russian gays or suspected gays are more and more common. Videos of young LGBT people being taunted and tortured have been widely distributed on the internet.